Pengaruh Kepuasan Konsumen yang Dimoderasi Biaya Perpindahan (Switching Cost) terhadap Niat Beralih (Switching Intention) pada Mahasiswa Pengguna Layanan Operator XL di Kota Denpasar - Yani, Ni Wayan Candra; Ekawati, Ni Wayan; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 3 No 6 (2014), 2014)
This study was conducted to determine whether the customer satisfaction and switching costs affect the switching intention on student operator XL users. The study was conducted in the city of Denpasar by taking a sample of 100 respondents using purposive sampling method and Quota Sampling. Collecting data using instruments with Guttman scale. Hypothesis testing is done with the help of software Moderated Regression Analysis smartPLS. Based on the results of the study, it was found that the variables of customer satisfaction and switching costs negatively affect the switching intention. In this study, switching costs are not shown to moderate the effect of customer satisfaction on switching intention. Suggestion for the company is doing better improvement of services through a single BTS installation and reduce the number of product lines to be more focused so that any consumer can feel satisfied and reluctant to switch to another provider.